CONFORMATION OF 6-MORPHOLINO-3-AZABICYCLO[3.1.0]HEXANE DERIVATIVES - Clark, Timothy; et al. (Journal of the Chemical Society, Perkin Transactions 2, 1993)
H-1 NMR spectroscopic studies established the presence of a chair conformation for endo-3-methyl-6-morpholino-3-azabicyclo[3.1.0]hexane derivatives 8a and b. This was additionally confirmed by an X-ray structural analysis of 8b. The diastereomers 10a,b and the N-demethyl-endo-morpholino compounds 9a,b, however, were found to prefer a boat conformation. The correlation between dihedral angles and ring buckle of 3-azabicyclo[3.1.0]hexane 4 was determined by MNDOC semiempirical calculations. Further structural information about this bicyclic system was obtained by HF/6-31 G* calculations for the 3-azabicyclo[3.1.0]hexane parent compounds 4 and 5.